Aggregation behavior of a gemini surfactant with a tripeptide spacer1. Issue 8 (28th February 2015) - Wang, Meina; Han, Yuchun; Qiao, Fulin; Wang, Yilin
<x xml:space="preserve">Abstract</x> A gemini surfactant with a tripeptide spacer shows strong pH-dependent and concentration-dependent aggregation behavior.